2018
DOI: 10.1038/s41420-018-0042-9
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial fission protein Drp1 inhibition promotes cardiac mesodermal differentiation of human pluripotent stem cells

Abstract: Human induced pluripotent stem cells (iPSCs) are a valuable tool for studying the cardiac developmental process in vitro, and cardiomyocytes derived from iPSCs are a putative cell source for personalized medicine. Changes in mitochondrial morphology have been shown to occur during cellular reprogramming and pluripotent stem cell differentiation. However, the relationships between mitochondrial dynamics and cardiac mesoderm commitment of iPSCs remain unclear. Here we demonstrate that changes in mitochondrial mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
56
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(65 citation statements)
references
References 37 publications
9
56
0
Order By: Relevance
“…[139][140][141] Changes in the dynamic mitochondrial network can also influence the identity, self-renewal capacity and commitment of stem cells, which reinforces the functional connection between morphology and metabolism, and which likely has implications for cancer (stem) cells as well. [142][143][144][145] Similar changes in the mitochondrial morphology have been observed also in T lymphocytes upon activation. Memory T cells on the other hand are quiescent, depend on oxidative phosphorylation, and hence showed a more fused morphology.…”
Section: Determinants Of the Mitochondrial Network Morphologysupporting
confidence: 74%
See 1 more Smart Citation
“…[139][140][141] Changes in the dynamic mitochondrial network can also influence the identity, self-renewal capacity and commitment of stem cells, which reinforces the functional connection between morphology and metabolism, and which likely has implications for cancer (stem) cells as well. [142][143][144][145] Similar changes in the mitochondrial morphology have been observed also in T lymphocytes upon activation. Memory T cells on the other hand are quiescent, depend on oxidative phosphorylation, and hence showed a more fused morphology.…”
Section: Determinants Of the Mitochondrial Network Morphologysupporting
confidence: 74%
“…Interestingly, cancer cells and stem cells share the same energy metabolism and hence share a similar mitochondrial morphology . Changes in the dynamic mitochondrial network can also influence the identity, self‐renewal capacity and commitment of stem cells, which reinforces the functional connection between morphology and metabolism, and which likely has implications for cancer (stem) cells as well . Similar changes in the mitochondrial morphology have been observed also in T lymphocytes upon activation.…”
Section: Mitochondrial Membrane Organizationmentioning
confidence: 63%
“…Further, we confirmed that pharmacological inhibition of Drp1 with Mdivi-1, a small molecule inhibitor of Drp1 (Bordt et al, 2017;Hoque et al, 2018) also markedly inhibited mitochondrial fission induced by chronic Ang II stimulation ( Fig 7C). Correspondingly, the mtROS production was also reduced obviously in si-Drp1-transfected ( Fig 7B) or…”
Section: Inhibition Of the Mitochondrial Fission Decreases Mitochondrsupporting
confidence: 74%
“…, IFN225,26 and Drp146 .Intriguingly, likewise for myosin-Va knockdown, Drp1 knockdown has also been shown to result in diminished tumorigenesis and features, such as increased OXPHOS and low clonogenic ability4,5,47 .Our data show that myosin-Va interacts with Spire1C and overexpression of Spire1C increases myosin-Va localization to mitochondria. Recently, non-mitochondrial Spire splice isoforms have been shown to interact with myosin-V motors32 .…”
supporting
confidence: 58%